Anterior Leaflet Laceration to Prevent Ventricular Outflow Tract Obstruction During Transcatheter Mitral Valve Replacement - Khan, Jaffar M.; Babaliaros, Vasilis C.; Greenbaum, Adam B.; Foerst, Jason R.; Yazdani, Shahram; McCabe, James M.; Paone, Gaetano; Eng, Marvin H.; Leshnower, Bradley G.; Gleason, Patrick T.; Chen, Marcus Y.; Wang, Dee Dee; et al. (Journal of the American College of Cardiology, 2019)
Left ventricular outflow tract (LVOT) obstruction is a leading cause of mortality and exclusion from transcatheter mitral valve replacement (TMVR). Intentional laceration of the anterior mitral valve leaflet to prevent LVOT obstruction (LAMPOON) is a transcatheter mimic of surgical chord-sparing leaflet resection. The purpose of this prospective multicenter trial was to study LAMPOON with transseptal (Edwards Lifesciences, Irvine, California) TMVR in annuloplasty rings or native mitral annular calcification (MAC). Subjects at high or extreme surgical risk and prohibitive risk of LVOT obstruction from TMVR were included. Eligibility was modified midtrial to exclude subjects with threatened LVOT obstruction from a Sapien 3 valve fabric skirt. The primary endpoint was procedure survival with successful LAMPOON, with successful TMVR, without reintervention, and with LVOT gradient <30 mm Hg (“optimal”) or <50 mm Hg (“acceptable”). Secondary endpoints included 30-day mortality and major adverse cardiovascular events. There was universal source-data verification and independent monitoring. All endpoints were independently adjudicated. Central laboratories analyzed echocardiogram and CT images. Between June 2017 and June 2018, 30 subjects were enrolled equally between the MAC and ring arms. LAMPOON traversal and midline laceration was successful in 100%. Procedure survival was 100%, and 30-day survival was 93%. Primary success was achieved in 73%, driven by additional procedures for paravalvular leak (10%) and high-skirt neo-LVOT gradients observed before a protocol amendment. There were no strokes. LAMPOON was feasible in native and annuloplasty ring anatomies in patients who were otherwise ineligible for treatment, with acceptable safety. LAMPOON was effective in preventing LVOT obstruction from TMVR. Despite LAMPOON, TMVR using Sapien 3 in annuloplasty rings and MAC still exhibits important limitations. (NHLBI DIR LAMPOON Study: Intentional Laceration of the Anterior Mitral Leaflet to Prevent Left Ventricular Outflow Tract Obstruction During Transcatheter Mitral Valve Implantation; NCT03015194) [Display omitted]